Importance of Investigating Linguacultural Variability in Learning Foreign Languages - Elnara Putayeva (Культура і мистецтво у сучасному світі)
The aim of the article is to investigate and prove the importance of linguocultural variability in the study of foreign languages. Results. In general, the question “Does language determine culture or culture determins language?” is still definitive as a fundamental question of new studies and investigations. Results show that these and other similar questions, as well as forms of interaction of language and culture, have recently become serious in a wider context, and have been a subject of discussion. As we know, language and culture both give distribution to the process of communication, and this interconnection helps foreign language learners to declare pragmatic, semantic and syntactic meanings in order to cooperate. Scientific novelty. This article is the author’s contribution to the study of the interaction of language and culture as two interrelated social phenomena that develop under conditions of mutual influence. Conclusions. Anyone who prefers to intercommunicate with success through language and culture must be aware of the differences between various cultures. In this example, anyone who evolves such communication should consider sociolinguistic, discourse, grammatical and strategic skills. As a rule, certain concepts may be specific to one culture, and might not be found in other cultures. This case can be considered as one of the crucial reasons of investigating cultural variability of certain language, and this is primary to success in learning foreign languages. While borderlines between languages are very clearly observed and followed, cultural boundaries only originate as a consequence of speakers’ cultural “collision”. Observations give us a chance to make a conclusion that in most countries, multiculturalism exists as a form of equal coexistence of different cultures within the same country. As far as people are related to various cultures, their cultural values are quite different. One can consider that numbers of values exist simply because they “disagree” from each other.